Toxologic Pathology of Piperazine Hydrate in Male Wild Pigeon at Basrah City/Southern Iraq - Bahaa, A. Al-Sereah; Suzan , A. Al-Azizz; Saleh, K. Majeed (International Journal of Poultry Science, 2011)
A three months Toxologic pathology study of piperazine hydrate in male wild pigeons by oral intubation were done. The study was done at three dosage levels as low (0.25 ml), intermediate (0.50 ml) and high (1 ml) with untreated control as fourth group. Clinical observation of treated pigeons did not show significant changes only the birds appeared to be quite after dosing for short time. Macroscopically no obvious changes could be detected. Microscopically, minimal diffuse vacculation of hepatocytes and varying number of parenchymal foci of inflammatory cells, mostly mononuclear cells. In treated birds a renal lesions were characterized by dilated cortical tubules mostly the proximal convoluted tubules with different levels. Heart showed foci/areas of infiltrating mononuclear cells between myocardial muscle cells with occasional vacuolated myocardial muscles cells. The pancreas showed a histopathological changes which were restricted to endocrine islets of langerhanse, which showed evidence of degeneration characterized by vacculation. The nervous system, there was no histopathological changes could be seen in cerebrum, but, vacculation of perking cells was noticed in cerebellum in some of treated birds, while, the most significant histopathological changes were in spinal cord as varying numbers of degenerate/vacuolated nerve fibers at all dosage levels but most severe at high dose levels, the other changes but to less extents were in sciatic nerve as there were only few to occasional degenerate/vacuolated nerve fibers with less severity as they were on the way of recovery.